Heart Rate Variability following Combined Aerobic and Resistance Training in Sedentary Hypertensive Women: A Randomised Control Trial - Masroor, Sidra (Indian Heart J, 2018)
OBJECTIVE: To investigate the effect of combined aerobic and resistance training (CART) on heart rate variability in sedentary, hypertensive women. PARTICIPANTS: A total of twenty-eight hypertensive (Stage 1 and 2) sedentary women (Age 40.54 ± 4.2 yrs; Height 155.14 ± 5.4 cm; Weight 70.96 ± 10.2 kg; BMI 29.6 ± 4.4; Duration of HTN: 6.43 ± 2.5 yrs) were recruited for the study. METHODS: Participants were randomly assigned to either the CART group that performed combined aerobic and resistance exercise of moderate intensity [aerobic exercise 50–80% of HR(max) (maximum heart rate) and resistance exercises at 50–80% of 1 Repetition Maximum (RM)], 5 times/week for 4 weeks, or to the control group that followed conventional treatment without any supervised exercise intervention. MAIN OUTCOME MEASURES: Resting blood pressure was measured and standard heart rate variability (HRV) indices were calculated using time domain (SDNN, pNN50, RMSSD) and frequency domain (LFnu, HFnu, LF/HF and TP) analysis. RESULTS: CART group demonstrated an increase in HFnu, TP, SDNN, and RMSSD, (p < 0.05) along with a significant decrease in LFnu, LF/HF ratio, systolic blood pressure, and diastolic blood pressure (p < 0.05). CONCLUSION: CART showed significant improvement in HRV parameters indicating vagal dominance in middle-aged hypertensive women. Therefore, exercise training in combined form (aerobic and resistance) may be incorporated in the management programs of the patients suffering from hypertension in order to augment improvement in their cardiac autonomic control.